2013
DOI: 10.5539/ass.v9n11p1
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Attitudes of Islamic Education Lecturers towards the Application and Knowledge of Multimedia in Teaching

Abstract: The advancement of technology has provided innovation in teaching and learning particularly at the Higher Learning Institutions. This article aims to identify the relationship between Islamic Education lecturers’ attitudes towards the application and knowledge of multimedia in teaching. This study is in the form of a survey conducted to obtain quantitative data. The data collected can explain the level of multimedia usage, the level of multimedia knowledge, and lecturers’ attitudes in the application of multim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Some studies, as referred by Noh et al (2013) showed that the usage of modern media and computerized graphics program could make the teaching and learning process, as well as the interaction inside the school environment a superlative and attractive scene. The accessibility of the organized media technologies everywhere in the school will work as an impetus could guarantee that the students study better.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies, as referred by Noh et al (2013) showed that the usage of modern media and computerized graphics program could make the teaching and learning process, as well as the interaction inside the school environment a superlative and attractive scene. The accessibility of the organized media technologies everywhere in the school will work as an impetus could guarantee that the students study better.…”
Section: Literature Reviewmentioning
confidence: 99%